Missed Nursing Care in a Sample of High-Dependency Italian Nursing Home Residents: Description of Nursing Care in Action. Issue 8 (December 2021) - Campagna, Sara; Basso, Ines; Vercelli, Elisa; Ranfone, Marco; Dal Molin, Alberto; Dimonte, Valerio; Di Giulio, Paola
Abstract : Objective: The aim of the study was to describe omitted or delayed nursing care (i.e., missed nursing care [MNC]) in a sample of Italian nursing homes (NHs). Methods: Nurses from 50 NHs located in Northern Italy selected the 20 most dependent residents in their care and reported instances of MNC for three to five consecutive shifts. They described the type of MNC, its cause(s), management, recurrence, and severity of possible consequences for the resident. Information on the residents and the NH was also collected. The instances of MNC were classified as potentially avoidable/preventable or not. Results: Overall, 266 (85.3%) of 312 nurses participated and 1000 residents were observed during 381 shifts (164 mornings, 164 afternoons, and 53 nights); 101 (38%) nurses reported 223 instances of MNC among 175 residents (17.5%). Ninety-seven omissions and 109 delays occurred during the day shift (56 omissions were delegated to the next shift). The most frequent MNC was drug administration (n = 71, 34.5%). In 24 (44.4%) of 54 instances of delayed drug administration, the delay was less than 30 minutes. Nurses rated approximately 20% of MNC (n = 41) as highly severe because of the discomfort caused to the resident, the clinical impact, or the repetitiveness of the situation. Nurses ascribed almost half of MNC (n = 100, 48.5%) to inadequate staffing, and they categorized 26 (11.6%) instances of MNC as unavoidable. Conclusions: The number of nurse-reported instances of MNC we reported was much lower than that previously collected with available instruments. Most MNC did not impact the comfort and safety of residents. A certain proportion of MNC was unavoidable.